Evaluation of Usability in LetsCode Digital Learning Media Using the Usability Testing Method and Use Questionnaire - Nadifa, Rahajeng Mufti; Pradana , Fajar; Bachtiar, Fitra Abdurrachman (Journal of Information Technology and Computer Science, 2024)
Basic Programming is one of the compulsory courses at the lecture level in the field of computer science. The problem that is often encountered in these courses is the low understanding of students towards the programming material provided. Digital learning media, namely the LetsCode website, was developed to become a learning support medium and increase students' understanding of basic programming. To find out how far learning media can meet user needs, a usability test is carried out to determine the usability level of the system. The research was conducted using the usability testing method using a Use Questionnaire for LetsCode website users. The criteria for the test respondents were students of the Information Technology Education Study Program, Brawijaya University, with a total of 30 respondents. From the results of the questionnaire test using the F test, it shows that the variables of expediency, ease of use, and ease of learning have a simultaneous effect on satisfaction. For the feasibility of getting a result of 88.43% of the overall usability aspect which shows the LetsCode website is in the very feasible category. The research was limited to the analysis of questionnaire data and did not enter the system development stage.